Functional genetic variants within the SIRT2 gene promoter in type 2 diabetes mellitus. (March 2018) - Liu, Tingting; Yang, Wentao; Pang, Shuchao; Yu, Shipeng; Yan, Bo
Highlights: SIRT2 gene promoter was analyzed in cohorts of T2D patients and controls. A total of 18 DSVs including 5 SNPs were found in this study population. Three novel and functional heterozygous DSVs were only identified in T2D patients. These DSVs may change SIRT2 levels and contribute to the T2D development. Abstract: Aims: Type 2 diabetes mellitus (T2D) is a common and complex metabolic diseases caused by interactions between environmental and genetic factors. Genome-wide association studies have identified more than 80 common genetic variants for T2D, which account for only ∼10% of the heritability of T2D cases. SIRT2, a member of NAD(+)-dependent class III deacetylases, is involved in genomic stability, metabolism, inflammation, oxidative stress and autophagy. In maintaining metabolic homeostasis, SIRT2 regulates adipocyte differentiation, fatty acid oxidation, gluconeogenesis, and insulin sensitivity. Thus, we hypothesized that DNA sequence variants (DSVs) in SIRT2 gene promoter may change SIRT2 levels, contributing to T2D. Methods: SIRT2 gene promoter was genetically and functionally analyzed in large cohorts of T2D patients (n = 365) and ethnic-matched controls (n = 358). Results: A total of 18 DSVs, including 5 SNPs, were identified in this study. Four novel heterozygous DSVs (g.38900912G > T, g.38900561C > T, g.38900359C > T and g.38900237G > A) were identified in four T2D patients, three of which (g.38900912G > T, g.38900359C > T and g.38900237G > A) significantly increased the transcriptional activity of the SIRT2 gene promoter in cultured pancreatic beta cells (P < .01). Seven novel heterozygous DSVs were only found in controls, and one heterozygous deletion DSV and five SNPs were found in both T2D patients and controls, which did not significantly affect SIRT2 gene promoter activity (P > .05). Conclusions: Our findings suggested that the DSVs may increase SIRT2 gene promoter activity and SIRT2 levels, contributing to T2D development as a risk factor.